A Narrative Review of Early Intervention for Eating Disorders: Barriers and Facilitators - Mills R; Hyam L; Schmidt U (Dove Medical Press, 2023)
Regan Mills,1 Lucy Hyam,1 Ulrike Schmidt1,2 1Department of Psychological Medicine, Centre for Research in Eating and Weight Disorders (CREW), King's College London, Institute of Psychiatry, Psychology and Neuroscience, London, UK; 2Eating Disorders Outpatient Service, South London and Maudsley NHS Foundation Trust, London, UKCorrespondence: Regan Mills, Department of Psychological Medicine, Centre for Research in Eating and Weight Disorders (CREW), King's College London, Institute of Psychiatry, Psychology and Neuroscience, London, UK, Email regan.mills@kcl.ac.ukAbstract: Eating disorders (EDs) are serious psychiatric illnesses that typically develop during adolescence and emerging adulthood. Early intervention is important for improved outcomes for young people with EDs, yet help-seeking is low and individuals often have a significantly protracted start to treatment, suggesting that early intervention is not well established in the ED field. Previous reviews on facilitators and barriers to early intervention for EDs largely cover perceived barriers related to patient variables and perspectives, whereas clinician-, service-, and healthcare system-related facilitators and barriers are less frequently reviewed. The aim of this review is to synthesize the literature on barriers to and facilitators of early intervention for EDs, regarding patient-, clinician-, service-, and healthcare system-related factors. A narrative review was conducted by searching for relevant peer-reviewed, English-language articles published up until July 2023 on PubMed and PsychINFO. The search was conducted in two steps. First, key search terms were used to identify existing reviews and meta-analyses on facilitators and barriers to early intervention for EDs. Then, additional search terms were added to search for primary and secondary research on patient/family, clinician, service, and healthcare system-related barriers and facilitators. The identified literature shows that, after overcoming intrinsic, motivational barriers (such as self-stigma, denial, and ambivalence), help-seeking individuals may be met with long service waiting lists and limited treatment options. Despite these barriers, there is ongoing research into early intervention in practice, which aims to reach underserved populations and facilitate early intervention despite high service demands and shortages of trained healthcare professionals. Funding for ED research and services has historically been low, and there is also a research-practice gap. This highlights the need for increased consideration of, and funding for early intervention for EDs, to remove barriers as well as facilitate discussions around how to make early intervention programs scalable and sustainable.Keywords: anorexia nervosa, bulimia nervosa, help-seeking, treatment seeking, mental health